Motivation of "Trust" in Education of Children Categories Asperger Disorder (AD) - Saidina Usman; Ridwan Ridwan; Siti Marwah; Nori Nopita Sari (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
Every child is unique and trustworthy from God, including children in the category of Asperger Disorder (AD). This study aims to analyze the experience of being a parent in educating â€œchildrenâ€ in the AD category. Islam teaches the concept of mandate as a parent. As a â€œknife of analysisâ€, T. Parsonâ€™s theory is used in observing the efforts of parents to realize a harmonious family in a â€œtrustfulâ€ frame. Obtaining data is done by using interview and observation techniques. The results showed that by considering children as â€œGodâ€™s mandateâ€, can raise awareness of educating and caring for children according to their needs. This is driven by factors of knowledge, appreciation, and religious practice of the childâ€™s parents.